(3OjhGf TeS GdOjf GdeYQha HGdVaOYs - (3eMeO Hf jhSa Hf YHO Gddg GdOeTbj, TeS GdOjf GdNjGW , GdVaOY,J (B756 (3g` s
(3ChdgG (B:s
(3CNj cd jhe di aDGO jQOY Ch MHjH jhOY s
(3BNQgG (B:s
(3hbdJ CjVkG EQJLGdkG hgj eeG JbOe fXeg ai ThGd SfI KdGK hSHYeGFI CQi GdOgQ bO CVfi YdjfG hYhVfG HYO GdeSQI HGdCSi s
(3GdfSNI HgG MhGTs
(3cJHJ Ydi QCS GdfSNI Cf gPG gh OjhGf GHf GdNjGW hgh NWCs
(3fSNI ecQQI Yf fSNI GdagQS HQbe (B325 (3COH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B153s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs